PERANCANGAN SISTEM INFORMASI KERJASAMA DENGAN FRAMEWORK LARAVEL PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Salma Nada Safira (2021)
Cooperation is an activity to obtain mutual agreement between the two parties. By utilizing website facilities, the creation of cooperation information system applications can provide convenience so as to speed up the collaboration data storage process for users. Using the new system is useful to help improve collaboration document data collection activities at the Faculty of Computer Science UPN Veteran Jakarta. The cooperation information system is made using the laravel framework, and is designed using the prototype method which has stages, namely gathering requirements, building prototyping, prototyping evaluation, coding system, system testing, system evaluation, and documentation. The result of this research is a website-based cooperation information system with the main features for data management of MoU, Cooperation Agreement (PKS), implementation of cooperation, monitoring and evaluation of cooperation, viewing and printing of the final recapitulation report. By using the cooperation information system can help employees in archiving cooperation documents.